Assessment of Inflammasome Formation by Flow Cytometry. (1st August 2016) - Sester, David P.; Zamoshnikova, Alina; Thygesen, Sara J.; Vajjhala, Parimala R.; Cridland, Simon O.; Schroder, Kate; Stacey, Katryn J.
Abstract: Inflammasomes are large protein complexes formed in response to cellular stresses that are platforms for recruitment and activation of caspase 1. Central to most inflammasome functions is the adapter molecule ASC (apoptosis‐associated speck‐like protein containing a caspase‐recruitment domain) that links the inflammasome initiator protein to the recruited caspases. ASC is normally diffuse within the cell but within minutes of inflammasome activation relocates to a dense speck in the cytosol. The dramatic redistribution of ASC can be monitored by flow cytometry using parameters of fluorescence peak height and width when immunostained or tagged with a fluorescent protein. This can be used to define cells with active inflammasomes within populations of primary macrophages and monocytes, allowing quantification of responses and flow‐sorting of responding cells. Protein structural requirements for ASC speck formation and recruitment of caspases to ASC specks can be assessed by expressing components in HEK293 cells. This provides rapid quantification of responding cell number and correlation with the expression level of inflammasome components within single cells. © 2016 by John Wiley & Sons, Inc.